Granulocyte Macrophage Colony-Stimulating Factor-Specific Autoantibodies and Cerebral Nocardia With Pulmonary Alveolar Proteinosis. (13th December 2020) - Berthoux, Charlotte; Mailhe, Morgane; Vély, Frédéric; Gauthier, Clarisse; Mège, Jean-Louis; Lagier, Jean-Christophe; Melenotte, Cléa
Abstract: In this study, we report the history of a 40-year-old man with a primary cerebral abscess caused by Nocardia abscessus that led to the discovery of autoimmune pulmonary alveolar lipoproteinosis (anti-granulocyte-macrophage colony-stimulating factor [GM-CSF] autoantibodies). Anti-GM-CSF autoantibodies promote immunodeficiency and should be monitored to prevent opportunistic and disseminated infections and to diagnose asymptomatic pulmonary alveolar lipoproteinosis.